High NF-κB and RAGE Expression in Fetal Membrane of Premature Rupture of Membrane (PROM) Subject - I Ketut Edy Sudiarta; Monicha Zalzabilla Aldinasyah; Cindy Jennilyn Candra; Supriyono Supriyono; Annisa Ullya Rasyida (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Premature Rupture of Membranes (PROM) is significantly linked to the infections-related maternal deaths. In the inflammatory process, the influencing stressor will stimulate the activation of Nuclear Factor Kappa B (NF-κB) and Receptor of Advanced Gyclation End product (RAGE). Yet up to date, the expression of NF-κB and RAGE in pregnant women with PROM are still rarely studied. Therefore, this study aimed to observe the differences of NF-κB and RAGE expression from PROM and non-PROM subjects.METHODS: This was a cross-sectional study involving 20 PROM subjects and 20 non-PROM subjects with infections and complications. Samples from the fetal membrane tissue of subjects were obtained and put into paraffin block preparation for the determination of NF-κB and RAGE expression. The detection of NF-κB and RAGE expression was conducted using immunohistochemical staining and observed under an upright light microscope. The expressions were later calculated using ImageJ software. RESULTS: Both NF-κB and RAGE expression were found to be higher in PROM subjects compare to the non-PROM subjects. The median of NF-κB in PROM and non-PROM subjects were 32.47±1.22 and 5.59±1.09, respectively (p=0.000). While the median of RAGE in PROM subjects was 53.58±3.46, and in non-PROM subjects was 11.64±2.49 (p=0.013).CONCLUSION: There is significant difference between NF-κB and RAGE expression in fetal membranes of PROM and non-PROM subjects. Therefore, the increased of NF-κB and RAGE expression can be used as a potential marker to detect complication of PROM.KEYWORDS: premature ruptures of membrane, non-premature ruptures of membrane, expression of NF-κB